Text Analysis Tools in ESP Teaching. Case Study - Alina Buzarna-Tihenea (Gălbează) (Ovidius University Annals: Economic Sciences Series, 2020)
This study, structured into two main sections (a theoretical part and a practical one) deals with the important role played by text analysis tools in ESP courses and seminars, when choosing appropriate teaching materials. The first section of the paper tackles theoretical concepts related to lexical cohesion, reiteration and collocations, and the roles played by vocabulary within discourse. The practical section analyses the results issued by two text analysis tools, i.e. Voyant Tools and SEO Scout, which processed an authentic corpus from the economic field, showing, among others, its lexical density, lexical diversity and collocates. These results provide vital information about the complexity of the analyzed corpus and about its appropriate use in ESP classes.